Wpływ świadków prawdy na zmagania duchowe św. Edyty Stein - Magdalena Raganiewicz (Wrocławski Przegląd Teologiczny, 2020)
Philosophy opened Edith Stein the perspective of Absolute, but it was the testimony of people, for whom faith was the centre of life, that decided of her baptism in the Catholic church. Phenomenology prepared her mentally to the later reception of God but it was the discovery of the depth and strength of individual people’s faith in Christ that determined her conversion into Catholicism. First Edith Stein was deeply moved by her lecturer Max Scheler, who clearly presented her the world of catholic values. Than she experienced profoundly the death of her friend Adolph Reinach. His funeral was a kind of a spiritual breakthrough, which she later described as her first meeting with Cross and its victory over death. An enormous influence on her soul had an anonymous woman whom Edith met in the cathedral. Edith Stein was astounded to see somebody who could stop in the middle of a busy day and spend some precious moments talking to Someone whose presence Edith had not perceived yet. The last witness of faith, Saint Teresa of Ávila, was the one who definitely convinced Edith Stein that the sense of life cannot be found anywhere else but in Christ. That Saint evidently proved that it is Jesus Christ who is the root of human existence; He is the Truth and the final answer to all people’s questions and doubts. The lecture of Saint Teresa’s autobiography was the final step on Edith Stein’s road to God. It resulted in baptism in the Catholic church which took place in January 1922.